The Effectiveness of Index Card Match Strategy to Improve the Eighth Graders’ Narrative Text Reading Comprehension in SMP N 2 Secang - Muhammad Rifqi Fauzi (International Journal of Research in Education, 2025)
Reading is essential for English language learners, as it enhances their comprehension and academic success. However, eighth-grade students at SMPN 2 Secang confronted challenges regarding reading comprehension, necessitating the implementation of suitable learning strategies to improve their understanding of texts. The objective of this study is to find out how effective is the use of Index Card Match strategy for students' reading comprehension improvement of narrative text and to find out the difference in reading comprehension of narrative text between the students who are taught by using Index Card Match strategy and STAD (Students Team Achievement Division) strategy. This study carried out quantitative research in Quasi-Experimental Design. Two classes were involved in this study, class VIII-F (experiment class) and class VIII-G (control class), with 65 students at SMP N 2 Secang. Reading comprehension tests were administered as the instrument for collecting data. The result of this study reveals that the experiment class showed an improvement in their posttest scores compared to the pretest. Moreover, the N-gain score results in 48.6013, meaning that the Index Card Match strategy falls into the less effective category. The independent sample t-test reveals a significant value of 0.071, which exceeds 0.05, indicating that the scores of the two groups are pretty similar, as well as the acceptance of H0 (null hypothesis). This study holds significant implications for enhancing teaching and learning practices in junior high school contexts. The findings can contribute to developing adaptive learning strategies, ultimately improving students' engagement and academic performance in reading.